Surveillance for Zika, Chikungunya, and Dengue Virus Incidence and RNAemia in Blood Donors at 4 Brazilian Blood Centers During 2016–2019. (11th June 2022) - Custer, Brian; Grebe, Eduard; Buccheri, Renata; Bakkour, Sonia; Stone, Mars; Capuani, Ligia; Alencar, Cecilia; Amorim, Luiz; Loureiro, Paula; Carneiro-Proietti, Anna Barbara; Mendrone-Junior, Alfredo; Gonçalez, Thelma; et al.
Abstract: Background: Except for public health case reports, the incidence of Zika virus (ZIKV), chikungunya virus (CHIKV), and dengue virus (DENV) infection are not available to assess the potential blood transfusion safety threat in Brazil. Methods: Pools of 6 donation samples (MP6) left over from human immunodeficiency virus, hepatitis B virus, and hepatitis C virus nucleic acid testing were combined to create MP18 pools (3 MP6 pools). Samples were tested using the Grifols triplex ZIKV, CHIKV, and DENV real-time transcription mediated amplification assay to estimate prevalence of RNAemia and incidence, and to compare these results to case reports in São Paulo, Belo Horizonte, Recife, and Rio de Janeiro, from April 2016 through June 2019. Results: ZIKV, CHIKV, and DENV RNAemia were found from donors who donated without overt symptoms of infection that would have led to deferral. The highest RNAemic donation prevalence was 1.2% (95% CI, .8%–1.9%) for DENV in Belo Horizonte in May 2019. Arbovirus infections varied by location and time of year, and were not always aligned with annual arbovirus outbreak seasons in different regions of the country. Conclusions: Testing donations for arboviruses in Brazil can contribute to public health. Transfusion recipients were likely exposed to ZIKV, CHIKV, and DENV viremic blood components during the study period. Abstract : Small pools of blood donor samples were tested for 3 arboviruses from April 2016 through June 2019. Identified infections varied by location and time of year in different regions of Brazil. Transfusion recipients were likely exposed to viremic blood components.